Diplomacy of influence and the digital sphere: the American strategy as a model (قضايا سياسية, 2022)
The recourse to diplomacy of influence to the digital field has been steadily increasing in all its types, such as applications, websites, social networks, and others. The huge and continuous development in technical capabilities and information technology has helped to bring about a radical change in diplomacy and the digital field and the emergence of new forms of it, the most important of which is digital diplomacy, which is One of the pillars of soft power in drawing relations between countries, as well as facilitating interaction between diplomats and Internet users to serve the foreign policy goals of countries, including the United States of America, "the subject of the study." In this context, the study touched on the issue of digital diplomacy in terms of its definition and importance in the foreign policy of the United States of America, leading to the various means of digital diplomacy to communicate with peoples for the purpose of influence, and to improve their bleak image.